Nursing and the collective action: accompanying child growth and development - Monteiro, Akemi Iwata; Macedo, Isabelle Pinheiro de; Santos, Ana Dulce Batista dos; Araújo, Wanessa Morais de (Rev Rene, 2011)
Accompanying the child growth and development (GD) is the guiding of basic health measures toward children. It is sometimes guided by the biomedical model. Trying to change this reality, this study is aimed to describe the implementation and development process of collective nursing monitoring of children’s GD. The study was developed according to the methodology of action research in a Family Health Unit in Natal/RN. It involved 4 nurses and 26 children caregivers from February through June 2010. In the situational diagnosis, the current reality of this monitoring is clear. In the planning, the proposal was presented to the unit staff and the strategy development was discussed. The implementation included the process description of the collective monitoring with the caregivers and nurses, in addition to evaluation. The educational group provides the nurse with a closer assistance to the user, adapting their actions in accordance with the users’ needs, making them protagonists of the act of caring.